Changes in the Role and Status of Women in the Nigerian Baptist Convention, 1914–2021 - Ojo, Matthews A. (Religions, 2024)
This study interrogates the changes in the roles and status of women in the Nigerian Baptist Convention, the largest Baptist denomination in Africa, with over 10,104 churches and about 11 million members. This paper attempts to answer the critical question of how and what processes stimulated and sustained the changes in the role and status of women among Nigerian Baptists from the colonial period to the contemporary era. This paper relied on primary source publications, interviews, and secondary publications, which provided invaluable data in analysing the historical and contemporary issues that have resulted in the changing roles and status of women in the Nigerian Baptist Convention. This study found that against patriarchal traditions that subordinated women to domestic activities in the homes, such factors as access to formal education, the formation of Women’s Missionary Union as an institutional framework to mainstream women’s religious activities, the employment of women with doctoral degrees as theological educators in Baptist seminaries in the 1980s, the ordination of women as Baptist ministers in the late 1990s, and the appointment of women to key positions in the Nigerian Baptist Convention were major factors that moved women from traditional subordinate positions to public leadership in the church. Generally, this has indirectly stirred a process of empowerment for women and agitation for equality with men in the NBC in the past one hundred years. This study concluded that this development has moved women from supportive roles to taking up significant leadership positions within an African patriarchal cultural system.